Consumer Overindebtedness And Regulation Of The Minimum Living Standard - Viviane Costa de Oliveira; Mateus Eduardo Siqueira Nunes Bertoncini (Lifestyle Journal, 2023)
Objective: This research aims to analyze consumer overindebtedness and the necessity of regulating the minimum living standard. It explores the consequences of easy credit and limited financial education, as well as the significance of consumer rights and legislation in maintaining a balanced consumer-corporate relationship.